Sentinel Events in Ophthalmology: Experience from Hong Kong - Shiu Ting Mak (Journal of Ophthalmology)
Purpose. To arouse ophthalmologists’ awareness in patient safety by reviewing sentinel events in Ophthalmology submitted to a web-based incident reporting system involving all public hospitals in Hong Kong. Methods. Sentinel events in Ophthalmology reported from November 2007 to October 2014 were identified and classified into different categories for further presentation and analysis. Key contributing factors attributing to the occurrence of the incidents were described. Suggestions aiming to prevent future occurrence of similar events were made. Relevant literature and case law were discussed. Results. Twelve sentinel events were included in this observational case series. They were classified into 4 main categories, namely “wrong eye” (5 cases, 41%), “wrong prescription” (3 cases, 25%), “wrong patient and surgery” (2 cases, 17%), and “retained surgical items” (2 cases, 17%). The key contributing factor leading to the occurrence of the incidents was largely human error. Increased staff awareness and proper time-out procedures were recommended to help prevent occurrence of these errors. Conclusion. Sentinel events in Ophthalmology do occur. Many of these incidents were attributed to human error. Surgeon’s awareness and willingness to prevent occurrence of sentinel events are warranted.